Electrochemical detection of protein glycosylation using lectin and protein–gold affinity interactions. Issue 8 (16th March 2016) - Yadav, Sharda; Carrascosa, Laura G.; Sina, Abu A. I.; Shiddiky, Muhammad J. A.; Hill, Michelle M.; Trau, Matt
Abstract : New electrochemical method to detect glycosylation of protein using lectin and protein gold interaction. Abstract : We report a new method for the electrochemical detection of glycosylation on proteins, which relies on lectin–protein interaction on a bare gold electrode. The target protein isolated by immunoaffinity is directly adsorbed onto a gold surface and its glycosylation status is retrieved by subsequent addition of specific lectins. The adsorption and subsequent recognition process is monitored electrochemically in the presence of [Fe(CN)6 ] 3−/4− redox system. By decoupling target protein capture from glycosylation read-out steps, this approach circumvents unwanted antibody–lectin crosstalk while enabling specific glycosylation detection of a glycoprotein in serum-spiked samples in less than 1 h.